Simultaneous, Single‐Cell Measurement of Messenger RNA, Cell Surface Proteins, and Intracellular Proteins. Issue 1 (6th January 2016) - Soh, Kah Teong; Tario, Joseph D.; Colligan, Sean; Maguire, Orla; Pan, Dalin; Minderman, Hans; Wallace, Paul K.
Abstract: Nucleic acid content can be quantified by flow cytometry through the use of intercalating compounds; however, measuring the presence of specific sequences has hitherto been difficult to achieve by this methodology. The primary obstacle to detecting discrete nucleic acid sequences by flow cytometry is their low quantity and the presence of high background signals, rendering the detection of hybridized fluorescent probes challenging. Amplification of nucleic acid sequences by molecular techniques such as in situ PCR have been applied to single‐cell suspensions, but these approaches have not been easily adapted to conventional flow cytometry. An alternative strategy implements a Branched DNA technique, comprising target‐specific probes and sequentially hybridized amplification reagents, resulting in a theoretical 8, 000‐ to 16, 000‐fold increase in fluorescence signal amplification. The Branched DNA technique allows for the quantification of native and unmanipulated mRNA content with increased signal detection and reduced background. This procedure utilizes gentle fixation steps with low hybridization temperatures, leaving the assayed cells intact to permit their concomitant immunophenotyping. This technology has the potential to advance scientific discovery by correlating potentially small quantities of mRNA with many biological measurements at the single‐cell level. © 2016 by John Wiley & Sons, Inc.